Design New Compound of Meisoindigo Derivative as Anti Breast Cancer Based on QSAR Approach - Agus Dwi Ananto; Handa Muliasari; Saprizal Hadisaputra (Jurnal Kimia Sains dan Aplikasi, 2020)
Design new compounds of Meisoindigo using the QSAR approach with semiempirical methods have been successfully made with better biological activity as anti-breast cancer results. The research method used to design the new compound of meisoindigo derivatives uses the semiempirical methods. The research procedure divide into tree step, molecular modeling, QSAR equation analysis, and design of new compounds. The PM3 method was chosen as a better method because it has model results that are more representative of physicochemical aspects. The selection of the best model is made by multilinear regression statistical analysis. New compounds derived from the design are expected to bind to the Cyclin-Dependent Kinase 4 (CDK4) enzyme that helps in the cell cycle to prevent cell division. Based on the design, the compound of (E)-2-(2-oxo-1-(2-(trifluoromethyl) benzyl)indolin-3-ylidene)-N-(quinoline-7-yl) acetamide choose as a new compound with more better biological activity (log 1/IC50 = 6.992) than before (log 1/IC50 = 5.823)